Curability of patients with lymph node metastases from extremity soft‐tissue sarcoma. Issue 23 (10th September 2020) - Basile, Georges; Mattei, Jean‐Camille; Alshaygy, Ibrahim; Griffin, Anthony M.; Catton, Charles N.; Chung, Peter W.; Shultz, David B.; Razak, Albiruni R. A.; Demicco, Elizabeth G.; Ferguson, Peter C.; Wunder, Jay S.
Abstract : Background: Lymph node metastases (LNM) rarely occur in adult extremity soft‐tissue sarcoma (STS), affecting approximately 5% of patients. To the authors' knowledge, few studies to date have evaluated the prognosis and survival of patients with LNM. Methods: A retrospective review was performed of a single‐center, prospectively collected STS database. Demographic, treatment, and oncologic data for patients with STS of the extremity with LNM were obtained from clinical and radiographic records. Results: Of 2689 patients with extremity STS, a total of 120 patients (4.5%) were diagnosed with LNM. LNM occurred most frequently among patients diagnosed with clear cell sarcoma (27.6%), epithelioid sarcoma (21.9%), rhabdomyosarcoma (17.3%), angiosarcoma (14.0%), and extraskeletal myxoid chondrosarcoma (9.3%). A total of 98 patients (81.7%) underwent LNM surgical resection. Patients with isolated LNM had a greater 5‐year overall survival (57.3%) compared with patients with American Joint Committee on Cancer (AJCC) eighth edition stage IV STS with only systemic metastases (14.6%) or both LNM and systemic disease (0%; P < .0001). Patients with isolated LNM had an overall survival rate (52.9%) similar to that of patients with localized AJCC stage III tumors (ie, large, high‐grade tumors) (49.3%) ( P = .8). Patients with late, isolated, metachronous LNM had a 5‐year overall survival rate (61.2%) that was similar to that of patients with isolated synchronous LNM at the time of presentation (53.6%) ( P = .4). Conclusions: Many different types of STS develop LNM. Patients with extremity STS with isolated LNM should not be considered as having stage IV disease as they are according to the current AJCC eighth edition classification because they have significantly better survival than those with systemic metastases. Patients with isolated, late, metachronous LNM have a survival similar to that of patients with isolated synchronous LNM at the time of presentation. Lay Summary: The results of the current study demonstrated that patients diagnosed with isolated lymph node metastases have a prognosis similar to that of patients diagnosed with localized American Joint Committee on Cancer stage III soft‐tissue sarcomas, which also equates to a significantly better overall survival compared with patients with systemic metastases. Therefore, the authors recommend modifications to the most recent eighth edition of the American Joint Committee on Cancer staging system to clearly distinguish patients with isolated lymph node metastases to acknowledge their better prognosis compared with those with systemic metastases. Abstract : The results of the current study demonstrate that patients diagnosed with isolated lymph node metastases have a prognosis similar to that of patients with localized American Joint Committee on Cancer (AJCC) stage III soft‐tissue sarcoma. Therefore, the authors recommend modifications to the most recent eighth edition of the AJCC staging system to clearly distinguish patients with isolated lymph node metastases to acknowledge their better prognosis compared with patients with systemic metastases.